2002
DOI: 10.1074/jbc.m200018200
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Signaling

Abstract: STAT transcription factors signal from the plasma membrane to the nucleus in response to growth factors and cytokines. We have investigated whether plasma membrane "rafts" are involved in cytokine-activated STAT signaling. Cytokine-free human hepatoma Hep3B cells or cells treated with interleukin-6 (IL-6) or orthovanadate (a general activator of STATs) were fractionated, and plasma membrane raft fractions were obtained by equilibrium sedimentation or flotation through discontinuous sucrose gradients using eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(71 citation statements)
references
References 34 publications
2
67
2
Order By: Relevance
“…Yet, in high-grade gliomas of both human and mouse tumours, we observed, in addition to the expected nuclear localization, a novel distinct plasma membrane-associated immunoreactivity for pY-STAT3. This observation is compatible with recent findings, suggesting that STAT proteins do not float solely as free monomers in the cytosol of mammalian cells but constitute high molecular mass protein complexes in lipid rafts (Sehgal et al, 2002) and/or dimerize prior to its activation (Kretzschmar et al, 2003). Raft proteins reside in specialized microdomains at the cell surface and are thought to play an important role in receptor signalling.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Yet, in high-grade gliomas of both human and mouse tumours, we observed, in addition to the expected nuclear localization, a novel distinct plasma membrane-associated immunoreactivity for pY-STAT3. This observation is compatible with recent findings, suggesting that STAT proteins do not float solely as free monomers in the cytosol of mammalian cells but constitute high molecular mass protein complexes in lipid rafts (Sehgal et al, 2002) and/or dimerize prior to its activation (Kretzschmar et al, 2003). Raft proteins reside in specialized microdomains at the cell surface and are thought to play an important role in receptor signalling.…”
Section: Discussionsupporting
confidence: 81%
“…Raft proteins reside in specialized microdomains at the cell surface and are thought to play an important role in receptor signalling. Intriguingly, treatment of cells with the raftbreaking compound methyl-b-cyclodextrin markedly inhibited IL-6-induced signalling (Sehgal et al, 2002). Recently, STAT3 dimerization and subcellular localization was studied in living cells (Kretzschmar et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that the cdk2-inhibitor p27 also may interact with signaling complexes by localizing to lipid rafts (Yaroslavskiy et al, 2001) Such localization could facilitate 'inside-out' signaling of cell cycle regulators to alter signal transduction at the membrane. Indeed, recent reports that Stat3 localizes to rafts (Sehgal et al, 2002) and that stat3 undergoes endocytosis during signaling (Bild et al, 2002) indicate that Stat3 may share topographic proximity with cdk2 and cdk2 inhibitors at the cell membrane. Our finding of Stat3 upregulation by cdk2 inhibitors is consistent with the report that antisense p27Kip1 decreased Stat3 activity in keratinocytes (Hauser et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the lipid-raft pathway is thought to play a critical role in various physiologic processes, such as protein trafficking, cell polarization and signal transduction (Le Roy and Wrana, 2005). Numerous reports have demonstrated that the lipid-raft pathway is crucial for signal transduction in several pathways such as the T-cell receptordependent signaling cascade (Langlet et al, 2000), B cell receptor signaling (Langlet et al, 2000), H-ras-mediated Raf activation (Parton and Hancock, 2004), tumor necrosis factor (TNF) receptor-mediated nuclear factor (NF)-kB activation (Legler et al, 2003), and interferon-g (IFN-g)-induced signal transducer and activator of transcription (STAT) signaling (Sehgal et al, 2002). Therefore, the lipid rafts represent critical sites for organizing and transmitting the extracellular signal into the cells.…”
Section: Introductionmentioning
confidence: 99%